Turgida turgida (Nematoda: Physalopteridae) parasitizing Water Oposssum (Chironectes minimus Zimmermann, 1780) in the Western Cordillera of Colombia and updated checklist of its associated parasites - Álvarez-Arellano, Diego; Pérez-Bedoya , José Leandro; Castaño, John Harold; Elejalde, Gerardo; Palacios-Castro, Shirley; Londoño-Raigosa, Manuela (Therya Notes, 2026)
Chironectes minimus is the only marsupial species of a semi-aquatic nature and is widely distributed in tropical and subtropical habitats from Central to South America. Although it has a wide distribution, little is known about aspects of its biology, as well as its parasites because it is considered a difficult species to sample. In this study, we report for the first time the presence of the nematode Turgida turgida in C. minimus in an area of the Western Cordillera in Colombia and compile a list of its other associated parasites. While preparing a specimen of C. minimus to enter the Mammal Collection of the Corporación Universitaria Santa Rosa de Cabal (CUS-M), six individuals of T. turgida were found when their stomach contents were checked. For scanning electron microscope analysis (SEM), all the samples were cleaned in saline solution and mounted on supports using carbon adhesive tape, coated with gold by sputtering in a cathodic sputtering machine. The nematodes found in the stomach of C. minimus were identified as Turgida turgida and correspond to five males and one female with a mean length of 2.45 cm and 4.59 cm, respectively. SEM revealed structures that characterize this species, such as ventrocaudal ornamentation patterns, and the presence of the 22nd broad, truncated caudal papilla on the male tail. We emphasize the importance of biological collections and recommend closer examination of specimens during the collection process, given the possibility of gathering relevant information on specimen-associated parasites, which could provide valuable insights into host-parasite relationships, ecological interactions and potential disease transmission pathways, ultimately allowing us to understand their implications for both public health and animal health.